Work-Family Conflict pada Pekerja Perempuan; Menyelami Peran Ganda antara Keluarga dan Tanggung Jawab Bekerja - Eliyana Eliyana; Nafilah (Faletehan Health Journal, 2025)
Working women frequently encounter work-family conflict as they strive to balance career demands with domestic responsibilities. This dual role creates significant pressure, which negatively impacts their health and well-being. This study aimed to explore the experiences and challenges of working women as they navigate these dual roles. A qualitative research design with a phenomenological approach was chosen for this study. Data was collected through in-depth, semi-structured open-ended interviews with five working mothers aged 25-45 who live with their children and husbands. All participants signed an informed consent form and agreed to have the 30–45minute interviews recorded. The interview transcripts underwent participant validation before being analyzed using a thematic analysis technique. The primary findings revealed that time management is the biggest challenge for these women. The struggle to balance roles includes managing time for effective communication, selecting the right parenting style, obtaining adequate rest, and completing all tasks. Their demanding schedules, heavy responsibilities, and exhausting workloads lead to a feeling that there is not enough time to successfully manage both their roles as mothers and employees. This condition can lead to health and social problems.